GPU-accelerated smoothed particle hydrodynamics modeling of jet formation and penetration capability of shaped charges. (November 2020) - Chen, Jian-Yu; Feng, Dian-Lei; Deng, Shu-Xin; Peng, Chong; Lien, Fue-Sang
Abstract: The prediction of the penetration of three-dimensional (3D) shaped charge into steel plates is a challenging task. In this paper, the smoothed particle hydrodynamics (SPH) method is applied to simulate the jet formation generated by the shaped charge detonation and its damage to steel plates. The Jones–Wilkins–Lee (JWL) equation of state (EOS), Tillotson EOS, and elastic–perfectly plastic constitutive model were incorporated into SPH for the modeling of explosive detonation and dynamic behavior of metal material. The compute unified device architecture (CUDA) parallel programming interface has been employed in SPH to improve the computational efficiency of SPH. Firstly, the constitutive models and EOSs are validated by 3D TNT slab detonation and aluminum–aluminum (Al–Al) high velocity impact. Then the jet formation of the shaped charge detonation and its penetration into the steel plates are investigated using the graphics processing unit (GPU)-accelerated SPH methodology. The numerical results of these test cases are compared against the published experimental data or analytical result, which shows that the GPU-accelerated SPH methodology is capable of tackling the 3D shaped charge detonation and penetration involving millions of particles with high computational efficiency.